2016
DOI: 10.1097/ijg.0000000000000316
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Palmitate and Carbomer Gel Protects the Conjunctiva of Patients With Long-term Prostaglandin Analogs Application

Abstract: Vitamin A palmitate and carbomer eye gel can effectively relieve dry eye symptom caused by long-term application of PGAs by increasing the GCs density and thereby reducing the toxicity to the conjunctiva. Vitamin A palmitate and carbomer eye gel may be valuable alternatives for glaucoma patients who prescribed long-term PGAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…This is emphasized by the fact that all retrieved studies on the association of green leafy vegetables with OAG found a significant association [ 22 , 23 , 43 , 44 ]. Another benefit patients with glaucoma may have from vitamin A is that vitamin A protects the conjunctiva and relieves dry eye symptoms caused by long-term application of IOP-lowering eye drops [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is emphasized by the fact that all retrieved studies on the association of green leafy vegetables with OAG found a significant association [ 22 , 23 , 43 , 44 ]. Another benefit patients with glaucoma may have from vitamin A is that vitamin A protects the conjunctiva and relieves dry eye symptoms caused by long-term application of IOP-lowering eye drops [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are required to assess the specific effects of forskolin on both the ocular surface and intraocular pressure. In patients on long-term prostaglandin analogues, preliminary studies show that vitamin A palmitate and carbomer gel appeared to relieve dry eye symptoms by increasing conjunctival goblet cell density 88 , though larger studies are required for further assessment of this supplement.…”
Section: Management Of Ocular Surface Disease In Conjunction With Glamentioning
confidence: 99%
“…Vitamin A has been used topically to protect the conjunctiva of patients with glaucoma and has resulted in improvement in dry eye symptoms (Cui et al. ). This study should be extended to other dry eye patients.…”
Section: Future Studies and Challengesmentioning
confidence: 99%